The income and food security impacts of soil and water conservation technologies in Tanzania - Manda, Julius; Tufa, Adane Hirpa; Alene, Arega; Swai, Elirehema; Muthoni, Francis; Hoeschle-Zeledon, Irmgard; Bekunda, Mateete (Frontiers in Sustainable Food Systems, 2023)
Using recent survey data, this study evaluates the adoption (as well as the duration of adoption) and the impacts of soil and water conservation technologies on income and food security in Tanzania. We employ a control function approach and instrumental variable regression models to estimate the average impacts and the instrumental variable quantile treatment effects model to analyze the distributional impacts of adoption. The results show that the adoption and duration of adopting soil and water conservation technologies had significant and positive effects on the total value of crop production and household income. Moreover, we find that the adoption and its duration had a significant and positive impact on the food security indicators—household dietary diversity, household food insecurity access scale, and household hunger scale. The results from the instrumental variable quantile treatment effects model also show that the impacts of adopting soil and water conservation technologies on the outcome variables are positive and significant, although they vary significantly across the income and food security distributions. The results indicate that even though adoption benefits households in both the lower and upper quantiles of the income and food security distributions, the marginal impacts of adoption are generally more significant for the households in the upper quantiles. The paper concludes with a discussion of the policy options for increasing and sustaining the adoption and impacts of soil and water conservation technologies in Tanzania.